Efficacy and Safety of Lumen-Apposing Stents for Management of Pancreatic Fluid Collections in a Community Hospital Setting - Rajat Garg; Abdelkader Chaar; Susan Szpunar; Babu P. Mohan; Mohammed Barawi (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Endoscopic ultrasound-guided transmural drainage and necrosectomy employing lumen-apposing metal stent (LAMS) are used for treating pancreatic fluid collections (PFCs) with excellent results from academic centers. Herein, we report the efficacy and safety of LAMS in the treatment of PFCs at a community hospital. Methods We retrospectively reviewed the etiology of pancreatitis, type and size of PFCs, length of procedure, technical success, clinical success, adverse events, and stent removal. The primary outcome was the rate of clinical success, and secondary outcomes were technical success and adverse events. Results Twenty-seven patients with a mean age of 54.1±6.5 years were included, 44% of which were men. The mean size of the PFCs was 9.7±5.0 cm (range, 3-21). The most common etiology of pancreatitis was alcohol (44%) followed by idiopathic causes (30%) and presence of gallstones (22%). The diagnosis was pseudocyst in 44.4% (12/27) and walled off necrosis in 55.6% (15/27) of patients. There was 100% technical success without any complications. Clinical success was achieved in 22 of 27 patients (81.5%) who underwent stent removal. Conclusions Our study is the first to report that endoscopic therapy of PFCs using LAMS is safe and effective even in a community hospital setting with limited resources and support compared to large academic centers.